Optimization of micro hot embossing process for manufacturing polymeric microfluidic devices with aluminum alloy die - Dong, Youqun (2014)
This project focuses on optimizing the micro hot embossing process of transferring micro features from an aluminum mold to a polymer substrate of COC with high fidelity. Effects on replication errors of parameters such as embossing temperature, load, holding time, and demolding temperature, were examined by design of experiment, the replication errors during this hot embossing process were modeled by response surface modeling, and optimal hot embossing process conditions were identified by analysis of the developed response surface models. It was found that temperature and load are the two most significant parameters for hot embossing. The orientation of the micro features with respect to the substrate material flow has influence on the width replication of the channels, which suggests that the property of the surface layer of COC substrate is anisotropic.